An Analysis of Psychology Characters in Novel “BUKAN PELAJAR BIASA” by Shandy Tan - Sabaswaly, Diana Reby; Momo, Lidia Lali (Journal of Language, Literature and Teaching, 2024)
This research aims to describe the psychology of the characters in the novel